Manajemen Pesantren Dalam Mengembangkan Enterpreneur Bidang Perikanan di Pondok Pesantren At-Tahdzib - Nurul 'Aini, Robi'ul Afif (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2022)
Pondok Pesantren Attahdzib as one of the Islamic educational institutions seeks to open up global discourse that occurs in the community around Islamic boarding schools and the general public and various problems that arise among students after leaving the pesantren, such as the lack of creativity of students after graduation in the sense that students do not know what to do. This is done, so that it can be said that students are less capable in solving their life problems, for that the Attahdzib Islamic Boarding School integrates its education pattern through various levels and majors in formal schools and those outside formal schools, as well as various exercises and patterns of habituation to living independently attached to them. in the daily life of the students which leads to the provision of enterprenuers. Especially in businesses in the field of fisheries such as learning the hatchery period and then ready to stock up on large ponds. Even the Attahdzib Islamic Boarding School has several pond units ranging from hatcheries to enlargements as a vehicle for learning skills, besides that it is the only Islamic boarding school for the first time in East Java that is successful and successful in hatching pomfret so that it can encourage the enthusiasm of students to participate in the world. enterprenuership (enterprenuer). Through this activity, the enterprenuerial interest of the santri is raised, and then directed towards the development of the management of economic enterprises when the santri return to the community. With the aim of output not only mastering the field of religion or the hereafter, but how the output can also survive the life with the various skills it has.